Optimal resource allocation in multiclass networks - Valeriy Naumov; Olli Martikainen (The Research Institute of the Finnish Economy (ETLA), 2011)
In this paper, we study resource allocation in multiclass networks having several types of flexible servers and general constraints on the number of servers at each station. Each job class is characterized by the station where the job is processed and by the amount of work allocated to that station upon job arrival. Servers may have different skills, working efficiency and resource requirements. We propose a simple method to calculate an upper bound for the maximum network throughput achievable with static resource allocation.
Keywords: C61; C62; C68; 330; resource allocation; flexible server; multiclass network; throughput; bottleneck; Unternehmensarchitektur; Allgemeines Gleichgewicht; Mathematische Optimierung; Theorie